Clinical presentation of herpes simplex virus infection mimicking neoplasia on the face of persons living with HIV. (February 2022) - Edwards, Robert Jeffrey; Dolly, Naomi; Musa, David; Edwards, Jonathan; Boyce, Gregory
The clinical presentations of herpes simplex virus (HSV) infections are varied and range from asymptomatic to a prodrome of tingling and burning followed by painful vesicles, erosions and ulcers. Resolution leads to latent infection of the sensory ganglia. HSV-1 is associated with most of the nongenital HSV–induced infections and HSV-2 is generally associated with anogenital lesions; however, lesions at either site may be caused by both viruses. In persons living with HIV (PLHIV), the lesions have been described as verrucous/hypertrophic, exophytic or vegetative and may suggest a neoplastic rather than an infective process and this can be a diagnostic dilemma in resource-limited countries with no access to confirmatory diagnostic testing for HSV. We report on two PLHIV who developed rapidly growing lesions on the face that clinically mimicked neoplasia but were found to be HSV-associated squamous proliferative lesions which responded to high dose acyclovir.